2019
DOI: 10.3390/su11216007
|View full text |Cite
|
Sign up to set email alerts
|

Driver Behavior Models for Heavy Vehicles and Passenger Cars at a Work Zone

Abstract: Traffic impact assessment is a key step in the process of work zone planning and scheduling for transportation agencies. Microscopic traffic simulation models enable transportation agencies to conduct detailed analyses of work zone mobility performance measures during the planning and scheduling process. However, traffic simulation results are valid only when the simulation model is calibrated to replicate driver behavior that is observed in the field. Few studies have provided guidance on the calibration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Work zone safety issues have been examined under different conditions and utilizing a range of crash-influencing factors. For example, the frequency and severity of rear-end crashes in work zones were analyzed by Qi et al ( 8 ), and the impact of heavy vehicles on work zone safety was assessed by Mahmood and Kianfar ( 19 ). The effects of environmental conditions, such as time of day and weather conditions, on safety have also been examined for work zone safety ( 20 , 21 ).…”
Section: Related Literaturementioning
confidence: 99%
“…Work zone safety issues have been examined under different conditions and utilizing a range of crash-influencing factors. For example, the frequency and severity of rear-end crashes in work zones were analyzed by Qi et al ( 8 ), and the impact of heavy vehicles on work zone safety was assessed by Mahmood and Kianfar ( 19 ). The effects of environmental conditions, such as time of day and weather conditions, on safety have also been examined for work zone safety ( 20 , 21 ).…”
Section: Related Literaturementioning
confidence: 99%
“…A multilayer feed-forward artificial neural network (ANN) model was developed by Du et al [20] to estimate the work zone delay and their results indicated that the ANN model outperformed traditional deterministic queuing models in terms of travel delay estimation accuracy. With respect to multi-model simulation, Mahmood et al [21] proposed separate driver behavior model parameters for heavy vehicles and passenger vehicles of work zone simulation, where the desired time headway was found to be 2.31 s for heavy vehicles and 1.53 s for passenger cars.…”
Section: Literature Review 21 Impact Assessment Of Work Zonesmentioning
confidence: 99%
“…changing the car's acceleration based on the speed and distance of the vehicle ahead (car-following models, [19], [20], [21]), or the event of lane changing based on the relative speed and available space in the overtaking lane (lane-changing models, [22]). However, more complex models are being developed to describe more complicated events, such as driver behaviour during unexpected lane closures [23].…”
Section: B Parametric Traffic Modelsmentioning
confidence: 99%